2011
DOI: 10.5223/kjpgn.2011.14.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Inflammatory Bowel Disease (IBD): Phenotypic, Genetic and Therapeutic Differences between Early-Onset and Adult-Onset IBD

Abstract: Inflammatory bowel disease (IBD) develops during childhood or adolescence in approximately 25% of patients with IBD. Recent studies on pediatric IBD have revealed that early-onset IBD has distinct phenotype differences compared to adult onset IBD. Pediatric early-onset IBD differs in many aspects including disease type, location of the lesions, disease behavior, gender preponderance and genetically attributable risks. This review examines the currently published data on the clinical, epidemiological and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 105 publications
1
19
0
Order By: Relevance
“…The most abundant bacteria phyla found in the large intestine of healthy adults are gram-negative Bacteroidetes and gram positive Firmicutes [1]. The intestinal microbiota are considered to act as a "metabolic organ", by deriving energy from nutrients that escape digestion in the upper gut.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant bacteria phyla found in the large intestine of healthy adults are gram-negative Bacteroidetes and gram positive Firmicutes [1]. The intestinal microbiota are considered to act as a "metabolic organ", by deriving energy from nutrients that escape digestion in the upper gut.…”
Section: Introductionmentioning
confidence: 99%
“…In the ACT1 and ACT2 studies, for patients with moderate or severe disease unresponsive to corticosteroids and immunomodulators, infliximab showed effects in mucosal healing and remission at 8 and 30 weeks [11], and a recent follow-up study reported a lower risk of bowel resection at 54 weeks [12]. Although research is limited in children and it may not be as effective as it is in Crohn's disease, infliximab is valued as a medication that can be used in patients with severe ulcerative colitis refractory to conventional treatment [1], and is reported to decrease the frequency of bowel resection [13]. In summary, the indications for treatment with infliximab are as follows: refractory Crohn's disease, corticosteroid dependent Crohn's disease, fistulizing Crohn's disease, severe ulcerative colitis, and inflammatory bowel disease with extraintestinal systemic symptom.…”
Section: The Effect Of Anti-tnf In Inf-lammatory Bowel Diseasementioning
confidence: 99%
“…Approximately 10 to 15% of patients diagnosed with inflammatory bowel disease, 25% of Crohn's disease, are diagnosed in childhood [1]. Although the pathogenesis of inflammatory bowel diseases is not very well understood, it is currently thought to be caused by the interaction between genetic factors, environmental factors, immune factors, and intestinal microbes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bowel diseases (IBDs) are complex, multifactorial disorders characterized by chronic relapsing intestinal inflammation [ 1 ]. IBD that develops in a child under 6 years of age is called very early onset-IBD (VEO-IBD) [ 2 3 ]. Because VEO-IBD starts earlier in life and has more resistance to immunosuppressive treatment, it is thought to have a strong association with genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%